Cesium tungsten bronze powder doped liquid crystal elastomer material and preparation method thereof
By doping cesium tungsten bronze nanoparticles in liquid crystal elastomer materials and using the Michael addition two-step preparation technology, the existing photothermal response liquid crystal materials are solved, and efficient and fast photothermal response and high reversible deformation capabilities are achieved, which is suitable for a variety of smart material applications.
Patent Information
- Application Number
- CN202510086528.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing photothermal response liquid crystal elastomer materials have problems such as low photothermal conversion efficiency, slow response time, and limited reversible deformation.
Liquid crystal oligomer and liquid crystal precursor solutions are prepared by doping cesium tungsten bronze nanoparticles into the liquid crystal elastomer material and using the Michael addition two-step method to prepare liquid crystal oligomer and liquid crystal precursor solutions. Combined with uniaxial stretching and ultraviolet curing technology, liquid crystal elastomer materials with excellent photothermal response performance were prepared.
The photothermal conversion efficiency and response speed of liquid crystal elastomer materials are improved, and the reversible deformation capability is enhanced. The photothermal response deformation reaches 20%-60%, which is suitable for soft robots, artificial muscles and wearable smart fabrics.
Smart Images

Figure CN119800541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photothermal response liquid crystal materials, and in particular to a liquid crystal elastomer material doped with cesium tungsten bronze powder and a preparation method thereof. Background Art
[0002] Liquid crystal elastomer polymers can respond to external stimuli such as heat, light, electricity, and magnetism, and have received extensive attention in the field of smart materials in recent years. Liquid crystal elastomers with multifunctional and programmable complex orientations can achieve multiple responses and complex shape changes, and have broad application prospects in soft robots, artificial muscles, wearable smart fabrics, and other fields.
[0003] At present, the photoresponsive liquid crystal elastomer materials are divided into photochemical isomerization responsive liquid crystal elastomers and photothermal responsive liquid crystal elastomers. Among them, photochemical isomerization responsive liquid crystal elastomers usually respond to ultraviolet light, which is easy to damage human tissue during practical application, limiting their application in wearable and other fields. Photothermal responsive liquid crystal elastomers have problems such as low photothermal conversion efficiency, narrow response band range, slow response time, and limited reversible deformation. Summary of the invention
[0004] An object of the first aspect of the present invention is to provide a liquid crystal elastomer material doped with cesium tungsten bronze powder to solve the technical problems of low photothermal conversion efficiency, slow response time and limited reversible deformation of liquid crystal elastomer materials in the prior art.
[0005] Another object of the first aspect of the present invention is to further improve the photothermal conversion efficiency and photothermal response speed of the liquid crystal elastomer material.
[0006] The second aspect of the present invention aims to provide a method for preparing the above-mentioned liquid crystal elastomer material.
[0007] According to the purpose of the first aspect of the present invention, the present invention provides a liquid crystal elastomer material doped with cesium tungsten bronze powder, wherein the liquid crystal elastomer material comprises cesium tungsten bronze nanoparticles with a mass fraction of any value between 1% and 20%, and the cesium tungsten bronze nanoparticles and acrylic liquid crystal monomers are prepared by a two-step Michael addition method to obtain a liquid crystal elastomer material with a photothermal response deformation amount of any value between 20% and 60%.
[0008] Optionally, the Michael addition two-step method includes a nucleophilic addition reaction, and the acrylic ester liquid crystal monomer is reacted with a chain extender and a catalyst to prepare a liquid crystal oligomer through the nucleophilic addition reaction.
[0009] Optionally, the acrylic ester liquid crystal monomer is any one of 1,4-bis-[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene and 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene.
[0010] Optionally, the chain extender is any one of 3,6-dioxa-1,8-octanedithiol, 2,2-oxybis(ethane-1-thiol), 2,2'-(1,2-ethylenedioxy)bisethanethiol, and 3-mercaptopropionic acid 2-ethyl-5,11-dioxo-11-[(2-oxotetrahydrothiophene-3-yl)amino]-2-{[(3-mercaptopropionyl)oxy]methyl}-4-oxa-8-thiaundecane-1-yl ester.
[0011] Optionally, the catalyst is any one of dipropylamine, n-butylamine, triethylamine, and 1,8-diazabicyclo[5.4.0]undec-7-ene.
[0012] Optionally, the size of the cesium tungsten bronze nanoparticles is any value between 20nm and 500nm.
[0013] Optionally, the Michael addition two-step method further comprises a crosslinking reaction, and the cesium tungsten bronze nanoparticles, the liquid crystal oligomers, the acrylic liquid crystal monomers and the chain extender, the catalyst, the crosslinker and the photoinitiator are crosslinked to prepare the liquid crystal elastomer material.
[0014] Optionally, the cross-linking agent is any one of pentaerythritol tetrakis-3-mercaptopropionate, pentaerythritol triacrylate and polyethylene glycol diacrylate.
[0015] Optionally, the photoinitiator is any one of 2-2-dimethoxy-2-phenylacetophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone.
[0016] According to the purpose of the second aspect of the present invention, the present invention also provides a method for preparing the liquid crystal elastomer material as described in any one of the above, comprising the following steps:
[0017] dispersing nano cesium tungsten bronze powder in an organic solvent to obtain a nano cesium tungsten bronze dispersant;
[0018] Dissolving an acrylic acid ester liquid crystal monomer, a chain extender and a catalyst in an organic solvent to prepare a liquid crystal oligomer;
[0019] Dispersing the nano-cesium tungsten bronze dispersant, the liquid crystal oligomer, the acrylate liquid crystal monomer, the chain extender, the catalyst, the cross-linking agent and the photoinitiator in an organic solvent to prepare a liquid crystal precursor solution;
[0020] Modeling the liquid crystal precursor solution to obtain liquid crystal elastomer fibers;
[0021] The liquid crystal elastomer fiber is subjected to uniaxial stretching and UV curing in sequence to prepare a cesium tungsten bronze-doped liquid crystal elastomer material.
[0022] The present invention sequentially prepares a liquid crystal oligomer and a liquid crystal precursor solution by a two-step Michael addition method, and prepares a liquid crystal elastomer material doped with cesium tungsten bronze powder by doping cesium tungsten bronze nanoparticles having a mass fraction of any value between 1% and 20% into the liquid crystal precursor solution. The liquid crystal elastomer material prepared in this embodiment has excellent photothermal response performance, photothermal conversion efficiency and high reversible deformation ability, can undergo photothermal response deformation under infrared light irradiation, and recover the deformation after the infrared light irradiation is removed, and the photothermal response deformation amount of the liquid crystal elastomer is any value between 20% and 60%, and can be applied to soft robots, artificial muscles, wearable smart fabrics and other fields.
[0023] Furthermore, the size of the cesium tungsten bronze nanoparticles of the present invention is any value between 20nm and 500nm. The cesium tungsten bronze nanoparticles within the above size range have a weak scattering effect on light, which helps to maintain the high transparency of the liquid crystal elastomer, and can more effectively absorb near-infrared rays, thereby improving the photothermal conversion efficiency and photothermal response speed of the liquid crystal elastomer material, and preventing the cesium tungsten bronze nanoparticles from being too large and affecting the elastic properties of the liquid crystal elastomer material.
[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings:
[0026] Figure 1 is a scanning electron microscope image of a liquid crystal elastomer material according to an embodiment of the present invention;
[0027] Figure 2 is a schematic flow chart of a method for preparing a liquid crystal elastomer material according to an embodiment of the present invention;
[0028] Figure 3 is the deformation amount of the liquid crystal elastomer material prepared according to Example 1 of the present invention at room temperature and under infrared light conditions;
[0029] Figure 4 is the deformation amount of the liquid crystal elastomer material prepared in Comparative Example 1 of the present invention at room temperature and under infrared light conditions;
[0030] Figure 5 is the deformation amount of the liquid crystal elastomer material prepared according to Comparative Example 2 of the present invention at room temperature and under infrared light conditions;
[0031] Figure 6 is a reversible deformation cycle diagram of the liquid crystal elastomer material prepared according to Example 1 of the present invention;
[0032] Figure 7 3 is a tensile stress-strain diagram of the liquid crystal elastomer material prepared according to Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0034] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] Figure 1 is a scanning electron microscope image of a liquid crystal elastomer material according to an embodiment of the present invention, Figure 2 is a schematic flow chart of a method for preparing a liquid crystal elastomer material according to an embodiment of the present invention.
[0038] like Figure 1 As shown, the present invention provides a cesium tungsten bronze powder doped liquid crystal elastomer material, the liquid crystal elastomer material includes cesium tungsten bronze nanoparticles with a mass fraction of any value between 1% and 20%, and the cesium tungsten bronze nanoparticles and acrylic liquid crystal monomers are prepared by a two-step Michael addition method to obtain a liquid crystal elastomer material with a photothermal response deformation amount of any value between 40% and 60%. Here, the mass fraction of cesium tungsten bronze nanoparticles in the liquid crystal elastomer can be 1%, 2%, 5%, 10%, 15% or 20%, or any value between 1% and 20%, and the prepared liquid crystal elastomer material can have a photothermal response deformation amount of 20%, 30%, 40%, 50% or 60% in the near-infrared light band, or any value between 20% and 60%.
[0039] In the present embodiment, a liquid crystal oligomer and a liquid crystal precursor solution are prepared in sequence by a two-step Michael addition method, and a cesium tungsten bronze powder-doped liquid crystal elastomer material is prepared by doping cesium tungsten bronze nanoparticles having a mass fraction of any value between 1% and 20%. The liquid crystal elastomer material prepared in the present embodiment has excellent photothermal response performance, photothermal conversion efficiency and high reversible deformation ability, can undergo photothermal response deformation under infrared light irradiation, and recover the deformation after the infrared light irradiation is removed, and the photothermal response deformation amount of the liquid crystal elastomer is any value between 20% and 60%, and can be applied to soft robots, artificial muscles, wearable smart fabrics and other fields.
[0040] In this embodiment, the mass fraction of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is any value between 1% and 20%, which can maximize the photothermal conversion efficiency, photothermal response speed, and photothermal response reversible deformation of the liquid crystal elastomer material. When the mass fraction of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is less than 1%, the content of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is too low, which will significantly reduce the photothermal response speed and photothermal conversion efficiency of the liquid crystal elastomer material. When the mass fraction of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is greater than 20%, the content of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is too high, and serious agglomeration will occur, resulting in a decrease in the optical properties, thermal response deformation properties, and mechanical properties of the liquid crystal elastomer material.
[0041] In a further embodiment, the Michael addition two-step method includes a nucleophilic addition reaction, and the liquid crystal oligomer is prepared by a nucleophilic addition reaction of an acrylate liquid crystal monomer with a chain extender and a catalyst. In this embodiment, when preparing a liquid crystal elastomer, the liquid crystal oligomer is first prepared by a nucleophilic addition reaction of an acrylate liquid crystal monomer with a chain extender and a catalyst, that is, through a nucleophilic addition reaction, the acrylate liquid crystal monomer and the chain extender are chemically bonded to achieve the extension and arrangement of the molecular chain, so that the liquid crystal oligomer has an ordered molecular structure and a higher molecular weight before the subsequent cross-linking reaction, which is helpful to form a more uniform and stable liquid crystal structure in the subsequent cross-linking reaction, and the liquid crystal oligomer has a higher molecular weight, which can give the liquid crystal elastomer material better mechanical properties, thermal stability and optical properties, thereby improving the photothermal responsiveness and shape memory of the liquid crystal elastomer material.
[0042] In a preferred embodiment, after the acrylate liquid crystal monomer and the chain extender in the nucleophilic addition reaction process are fully dissolved, a catalyst is added to carry out a nucleophilic addition reaction, so that the acrylate liquid crystal monomer and the chain extender can react completely under the action of the catalyst, thereby improving the resource utilization of the acrylate liquid crystal monomer and the chain extender and reducing raw material waste.
[0043] In a further embodiment, the acrylate liquid crystal monomer is any one of 1,4-bis-[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene and 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene. In this embodiment, the above two acrylate liquid crystal monomers both contain acryloyloxy groups and have good photosensitivity, so as to form a tight molecular chain structure under the action of a chain extender, and rapidly undergo a cross-linking reaction under the action of a photoinitiator to form a stable liquid crystal network structure, thereby improving the thermal stability and light response ability of the liquid crystal network structure. In addition, the acrylate liquid crystal monomer has a specific liquid crystal phase behavior and can form a stable liquid crystal state within a certain temperature range. By adjusting the structure and proportion of the acrylate monomer, the liquid crystal phase behavior of the liquid crystal elastomer can be precisely controlled.
[0044] In this embodiment, the functional groups such as benzoyloxy and acryloyloxy in the acrylic ester liquid crystal monomer can form hydrogen bonds, van der Waals forces and other intermolecular interactions with other components. The existence of these interactions enhances the connection strength between the liquid crystal elastomer molecular chains, so that the prepared liquid crystal elastomer material can maintain better elasticity and shape stability when subjected to external forces. In other words, after the liquid crystal elastomer material is irradiated with infrared light, a certain amount of photothermal response deformation occurs, and after the infrared light is removed, the liquid crystal elastomer material can restore the deformation, so that the prepared liquid crystal elastomer material has a high reversible deformability.
[0045] In a further embodiment, the chain extender is any one of 3,6-dioxa-1,8-octanedithiol, 2,2-oxybis(ethane-1-thiol), 2,2'-(1,2-ethylenedioxy)bisethanethiol, 3-mercaptopropionic acid 2-ethyl-5,11-dioxo-11-[(2-oxotetrahydrothiophene-3-yl)amino]-2-{[(3-mercaptopropionyl)oxy]methyl}-4-oxa-8-thiaundecane-1-yl ester. In this embodiment, the thiol group and disulfide bond in the above chain extender can enhance the crosslinking degree of the polymer, thereby improving the stability and structural strength of the liquid crystal oligomer, and the chain extender containing a dioxy structure and a complex functional group can improve the thermal stability, flexibility and chemical resistance of the liquid crystal oligomer.
[0046] In a further embodiment, the catalyst is any one of dipropylamine, n-butylamine, triethylamine, and 1,8-diazabicyclo[5.4.0]undec-7-ene. In this embodiment, dipropylamine, n-butylamine, and triethylamine can accelerate the nucleophilic addition reaction by reducing the activation energy of the reaction, thereby promoting the formation of liquid crystal oligomers, and 1,8-diazabicyclo[5.4.0]undec-7-ene can significantly accelerate the nucleophilic addition reaction, improve the yield and purity of the product, thereby increasing the amount of effective reactants in the subsequent cross-linking reaction, and further increasing the yield of the liquid crystal elastomer material.
[0047] In this embodiment, in the preparation of liquid crystal oligomers, the acrylic ester liquid crystal monomer is 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene, the chain extender is 3,6-dioxa-1,8-octanedithiol, and the catalyst is dipropylamine to prepare a liquid crystal oligomer of pentaerythritol tetra-3-mercaptopropionate. The structural formula of pentaerythritol tetra-3-mercaptopropionate is as follows:
[0048]
[0049] In a further embodiment, the size of the cesium tungsten bronze nanoparticles is any value in the range of 20nm-500nm, that is, the size of the cesium tungsten bronze nanoparticles can be 20nm, 50nm, 100nm, 150nm, 200nm, 300nm, 400nm or 500nm, or any value in the range of 20nm-500nm. In this embodiment, the cesium tungsten bronze nanoparticles within the above size range have a weak scattering effect on light, which helps to maintain the high transparency of the liquid crystal elastomer, and can more effectively absorb near-infrared rays, improve the photothermal conversion efficiency and photothermal response speed of the liquid crystal elastomer material, and prevent the cesium tungsten bronze nanoparticles from being too large to affect the elastic properties of the liquid crystal elastomer material. Here, the cesium tungsten bronze nanoparticles can be prepared by a solvent thermal method or a high-temperature sintering method.
[0050] like Figure 1As shown, in a further embodiment, the Michael addition two-step method also includes a cross-linking reaction, and the cesium tungsten bronze nanoparticles, liquid crystal oligomers, acrylate liquid crystal monomers and chain extenders, catalysts, cross-linkers and photoinitiators are cross-linked to prepare liquid crystal elastomer materials. In this embodiment, after the acrylate liquid crystal monomers react with the chain extenders to form liquid crystal oligomers, the liquid crystal oligomers react with the cesium tungsten bronze nanoparticles, acrylate liquid crystal monomers, chain extenders, catalysts, photoinitiators and cross-linkers to form a cross-linked network structure, so that the cesium tungsten bronze powder is evenly dispersed in the gaps of the cross-linked network structure, and because a molecular chain structure with a higher molecular weight has been formed before the cross-linking reaction, it is easier to form a cross-linked network structure in the cross-linking reaction, which helps to avoid the increase in reaction complexity and the generation of by-products due to too many components in a single reaction step, and further improves the product purity of the liquid crystal elastomer material.
[0051] In a further embodiment, the crosslinking agent is any one of pentaerythritol tetra-3-mercaptopropionate, pentaerythritol triacrylate and polyethylene glycol diacrylate. In this embodiment, pentaerythritol tetra-3-mercaptopropionate can be crosslinked with a liquid crystal base monomer containing a carbon-carbon double bond through a thiol-ene click chemistry reaction. The crosslinking reaction is controllable and efficient, and a stable crosslinking network can be formed. The prepared liquid crystal elastomer usually has high heat resistance and glass transition temperature. Pentaerythritol triacrylate has multiple acrylate functional groups, which can be crosslinked through free radical polymerization, and the crosslinked liquid crystal elastomer has better wear resistance and chemical resistance while maintaining liquid crystal properties. Polyethylene glycol diacrylate has acrylate functional groups, which can be crosslinked through free radical polymerization, and the crosslinked liquid crystal elastomer has better biocompatibility and processability while maintaining liquid crystal properties. Here, the crosslinking agent can also be other crosslinking agents that can promote the crosslinking reaction between acrylate liquid crystal monomers and liquid crystal oligomers, and the corresponding crosslinking agent can be selected according to the characteristics of the required liquid crystal elastomer material.
[0052] In a further embodiment, the photoinitiator is any one of 2-2-dimethoxy-2-phenylacetophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone. In this embodiment, different photoinitiators have different reactivity and absorption wavelengths, and can induce cross-linking reactions with different cross-linking degrees, and can be selected according to specific cross-linking reaction conditions and the required properties of the prepared liquid crystal elastomer material.
[0053] like Figure 2 As shown, the present invention also provides a method for preparing any of the above liquid crystal elastomer materials, comprising the following steps:
[0054] Step S100: dispersing nano-cesium tungsten bronze powder in an organic solvent to obtain a nano-cesium tungsten bronze dispersant;
[0055] Step S200: dissolving an acrylic ester liquid crystal monomer, a chain extender and a catalyst in an organic solvent to prepare a liquid crystal oligomer;
[0056] Step S300: dispersing nano-cesium tungsten bronze dispersant and liquid crystal oligomers, acrylate liquid crystal monomers, chain extenders, catalysts, crosslinking agents and photoinitiators in an organic solvent to prepare a liquid crystal precursor solution;
[0057] Step S400: Modeling the liquid crystal precursor solution to obtain liquid crystal elastomer fibers;
[0058] Step S500: sequentially performing uniaxial stretching and UV curing on the liquid crystal elastomer fiber to prepare a cesium tungsten bronze-doped liquid crystal elastomer material.
[0059] In this embodiment, when preparing the liquid crystal elastomer material, the nano cesium tungsten bronze powder is first dispersed in an organic solvent to obtain a nano cesium tungsten bronze dispersant, and then the acrylate liquid crystal monomer, chain extender and catalyst are dissolved in the organic solvent to prepare a liquid crystal oligomer, and then the nano cesium tungsten bronze dispersant and liquid crystal oligomer, acrylate liquid crystal monomer, chain extender, catalyst, crosslinker and photoinitiator are dispersed in the organic solvent to prepare a liquid crystal precursor solution, and the prepared liquid crystal precursor solution is modeled to obtain a liquid crystal elastomer fiber, and finally the liquid crystal elastomer fiber is sequentially uniaxially stretched and UV-cured to prepare a cesium tungsten bronze doped liquid crystal elastomer material. Here, the organic solvent used to dissolve the cesium tungsten bronze powder is any one of dichloromethane, dimethyl sulfoxide, toluene, N, N-dimethylformamide, and tetrahydrofuran.
[0060] In this embodiment, cesium tungsten bronze nanoparticles are doped into a liquid crystal elastomer material, and a two-step Michael addition method is used in the preparation process, that is, first, a nucleophilic addition reaction is performed using an acrylate liquid crystal monomer, a chain extender and a catalyst to prepare a liquid crystal oligomer, and then the prepared cesium tungsten bronze dispersant is used with a liquid crystal oligomer and an acrylate liquid crystal monomer, a chain extender, a catalyst, a crosslinking agent and a photoinitiator to prepare a liquid crystal precursor solution through a crosslinking reaction, and the liquid crystal Zener body solution is modeled, uniaxially stretched and UV-cured in sequence to prepare a liquid crystal elastomer material doped with cesium tungsten bronze nanoparticles having a light-thermal response deformation amount of any value between 20% and 60%.
[0061] The present application will be further described in detail below with reference to specific embodiments.
[0062] Example 1
[0063] First, 0.072g of nano-cesium tungsten bronze powder was dispersed in 2g of organic solvent dichloromethane to prepare cesium tungsten bronze dispersant, 3g of acrylate liquid crystal monomer 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene RM82 and 0.82g of chain extender 3,6-dioxa-1,8-octanedithiol were dispersed in 11g of dichloromethane, and after being fully dissolved, 0.096g of catalyst dipropylamine was added, and the mixture was stirred in a water bath at 40°C for 24h to prepare liquid crystal oligomers. Nano-cesium tungsten bronze dispersant and 1g of liquid crystal oligomers, 0.5g of acrylate liquid crystal monomer 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene RM82 and 0.82g of chain extender 3,6-dioxa-1,8-octanedithiol were dispersed in 11g of dichloromethane. The liquid crystal precursor solution is prepared by mixing 0.01 g of 3,6-dioxa-1,8-octanedithiol, 0.2 g of pentaerythritol tetra-3-mercaptopropionate as a crosslinker, and 0.02 g of 2-2-dimethoxy-2-phenylacetophenone as a photoinitiator to prepare a liquid crystal precursor solution, adding the liquid crystal precursor solution to a syringe, and slowly extruding the liquid crystal precursor material through a nozzle by a syringe pump to prepare a liquid crystal elastomer fiber, and then uniaxially stretching the liquid crystal elastomer fiber to 200% of the initial length, and UV curing the material by UV curing technology to maintain the orientation of the liquid crystal unit, and preparing a cesium tungsten bronze doped liquid crystal elastomer material. The mass fraction of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material in this embodiment is 4wt%.
[0064] Example 2
[0065] The difference between Example 2 and Example 1 is that the mass fraction of cesium tungsten bronze nanoparticles is 8wt%, the acrylic ester liquid crystal monomer is 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, the mass of the chain extender is 0.93g, and the uniaxial stretching is 250% of the initial length.
[0066] Example 3
[0067] The difference between Example 3 and Example 1 is that the mass fraction of the cesium tungsten bronze nanoparticles is 16 wt %.
[0068] Example 4
[0069] The difference between Example 4 and Example 1 is that the mass fraction of cesium tungsten bronze nanoparticles is 20wt%, the catalyst is n-butylamine, and the mass of the catalyst is 0.1g.
[0070] Comparative Example 1
[0071] The only difference between Comparative Example 1 and Example 1 is that the liquid crystal elastomer material does not contain cesium tungsten bronze nanoparticles.
[0072] Comparative Example 2
[0073] The only difference between Comparative Example 2 and Example 1 is that the mass fraction of the cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is 25 wt %.
[0074] First, the liquid crystal elastomer materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested for the photothermal response deformation amount, and the photothermal response deformation amount test results of the liquid crystal elastomer materials shown in Table 1 were obtained.
[0075] Table 1. Results of the photothermal response deformation of the liquid crystal elastomer materials in Examples 1-4 and Comparative Examples 1-2
[0076] Mass fraction of cesium tungsten bronze nanoparticles Photothermal response deformation Example 1 4wt% 30% Example 2 8wt% 42% Example 3 16wt% 55% Example 4 20wt% 32% Comparative Example 1 0 0 Comparative Example 2 25wt% 15%
[0077] As shown in Table 1, when the mass fraction of cesium tungsten bronze nanoparticles is between 1% and 20%, the photothermal response deformation of the prepared liquid crystal elastomer material is between 20% and 60%, indicating that the liquid crystal elastomer material prepared by the present invention has excellent photothermal response speed and photothermal conversion efficiency.
[0078] Figure 3 is the deformation of the liquid crystal elastomer material prepared according to Example 1 of the present invention at room temperature and under infrared light conditions, Figure 4 is the deformation amount of the liquid crystal elastomer material prepared in Comparative Example 1 of the present invention at room temperature and under infrared light conditions, Figure 5 is the deformation amount of the liquid crystal elastomer material prepared in Comparative Example 2 of the present invention at room temperature and under infrared light conditions, Figure 6 is a reversible deformation cycle diagram of the liquid crystal elastomer material prepared according to Example 1 of the present invention, Figure 7 3 is a tensile stress-strain diagram of the liquid crystal elastomer material prepared according to Example 1 and Comparative Example 1 of the present invention.
[0079] like Figure 3 As shown in the figure, the length of the liquid crystal elastomer material prepared in Example 1 is 20 mm at room temperature, and the length of the liquid crystal elastomer material is reduced to 14 mm after infrared light irradiation, and the elastic deformation is restored to 6 mm after the infrared light irradiation is removed, indicating that the liquid crystal elastomer material prepared in Example 1 has strong photothermal response performance and reversible deformation performance. Figure 4 As shown) and Comparative Example 2 (as Figure 5 The deformation amounts of the liquid crystal elastomer material prepared by the method as shown in the figure before and after infrared irradiation are 0 and 3 mm, respectively, indicating that the photothermal response performance is poor when the mass fraction of cesium tungsten bronze nanoparticles in the liquid crystal elastomer material is lower than 1% or higher than 20%.
[0080] like Figure 6As shown, the driving strain of the liquid crystal elastomer material prepared in Example 1 remains basically unchanged after multiple infrared light irradiation and removal, indicating that the liquid crystal elastomer material of the present invention has high reversible deformation performance and can undergo multiple reversible deformations under infrared light irradiation.
[0081] like Figure 7 As shown, the tensile elongation at break of the liquid crystal elastomer material prepared in Example 1 is significantly higher than that in Comparative Example 1, and its shrinkage is significantly lower than that in Comparative Example 1, indicating that the liquid crystal elastomer material prepared in Example 1 has stronger elastic deformation performance.
[0082] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0083] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A liquid crystal elastomer material doped with cesium tungsten bronze powder, characterized in that: The liquid crystal elastomer material comprises cesium tungsten bronze nanoparticles with a mass fraction of any value between 1% and 20%. The cesium tungsten bronze nanoparticles and acrylic liquid crystal monomers are prepared by a two-step Michael addition method to obtain a liquid crystal elastomer material with a photothermal response deformation amount of any value between 20% and 60%.
2. The liquid crystal elastomer material according to claim 1, characterized in that: The Michael addition two-step method includes a nucleophilic addition reaction, and the acrylic ester liquid crystal monomer, the chain extender and the catalyst are reacted with the nucleophilic addition reaction to prepare a liquid crystal oligomer.
3. The liquid crystal elastomer material according to claim 2, characterized in that: The acrylic ester liquid crystal monomer is any one of 1,4-bis-[4-(6-acryloxyhexyloxy)benzoyloxy]-2-methylbenzene and 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene.
4. The liquid crystal elastomer material according to claim 3, characterized in that: The chain extender is any one of 3,6-dioxa-1,8-octanedithiol, 2,2-oxybis(ethane-1-thiol), 2,2'-(1,2-ethylenedioxy)bisethanethiol, and 3-mercaptopropionic acid 2-ethyl-5,11-dioxo-11-[(2-oxotetrahydrothiophene-3-yl)amino]-2-{[(3-mercaptopropionyl)oxy]methyl}-4-oxa-8-thiaundecane-1-yl ester.
5. The liquid crystal elastomer material according to claim 4, characterized in that: The catalyst is any one of dipropylamine, n-butylamine, triethylamine and 1,8-diazabicyclo[5.4.0]undec-7-ene.
6. The liquid crystal elastomer material according to any one of claims 1 to 5, characterized in that: The size of the cesium tungsten bronze nanoparticles is any value between 20nm and 500nm.
7. The liquid crystal elastomer material according to claim 6, characterized in that: The Michael addition two-step method also includes a cross-linking reaction, and the cesium tungsten bronze nanoparticles, the liquid crystal oligomers, the acrylic liquid crystal monomers and the chain extender, the catalyst, the cross-linking agent and the photoinitiator are used to prepare the liquid crystal elastomer material through the cross-linking reaction.
8. The liquid crystal elastomer material according to claim 7, characterized in that: The cross-linking agent is any one of pentaerythritol tetrakis-3-mercaptopropionate, pentaerythritol triacrylate and polyethylene glycol diacrylate.
9. The liquid crystal elastomer material according to claim 8, characterized in that: The photoinitiator is any one of 2-2-dimethoxy-2-phenylacetophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone.
10. A method for preparing the liquid crystal elastomer material according to any one of claims 1 to 9, characterized in that: The steps include: dispersing nano cesium tungsten bronze powder in an organic solvent to obtain a nano cesium tungsten bronze dispersant; Dissolving an acrylic acid ester liquid crystal monomer, a chain extender and a catalyst in an organic solvent to prepare a liquid crystal oligomer; Dispersing the nano-cesium tungsten bronze dispersant, the liquid crystal oligomer, the acrylate liquid crystal monomer, the chain extender, the catalyst, the cross-linking agent and the photoinitiator in an organic solvent to prepare a liquid crystal precursor solution; Modeling the liquid crystal precursor solution to obtain liquid crystal elastomer fibers; The liquid crystal elastomer fiber is subjected to uniaxial stretching and UV curing in sequence to prepare a cesium tungsten bronze-doped liquid crystal elastomer material.
Citation Information
Patent Citations
Variable valency metal catalyzed and doped tungsten bronze nano-short rod particle and preparation method thereof
CN105668632A
Bismuth-doped liquid crystal elastomer material as well as preparation method and application thereof
CN116253821A
Preparation method and application of liquid crystal elastomer plant bionic tendrils
CN116657269A
Flexible photo-thermal electric device based on cesium tungsten bronze as well as preparation method and application of flexible photo-thermal electric device
CN117119867A
Adhesive liquid crystal elastomer capable of realizing reversible rotation and preparation method thereof
CN118599116A